‎Artificial Intelligence in the Service of Interpreting: The Hajj Season in the Kingdom of Saudi Arabia (2024–2025) as an Applied Case Study - Al-Shahrani, Hamud Nasser (Arab Journal for Sciences and Research Publishing, 2025)
The study aims to: (1) evaluate the effectiveness of AI tools in supporting interpreting services, (2) identify their practical applications during the Hajj season, and (3) analyze their capacity to operate in complementarity with human interpreters. It is based on the hypothesis that properly integrated AI technologies can enhance the accuracy, quality, and efficiency of interpreting without replacing professional interpreters. Methodologically, the study adopts a descriptive-analytical approach, combining a critical review of relevant Arabic and international literature with an analytical examination of initiatives implemented under Saudi Arabia’s “Smart Hajj’’ programs. The results indicate that AI systems have shown considerable effectiveness in facilitating real-time multilingual communication, particularly in urgent and operational contexts. However, the findings reveal significant limitations in culturally and religiously sensitive situations, where AI-generated outputs often lack contextual depth and require human intervention. These results confirm that optimal performance is achieved when AI solutions complement human expertise, especially in interpreting religious terminology and managing culturally nuanced interactions, Based on the findings, the study recommends providing specialized training programs to improve interpreters’ competence in using AI-based tools, strengthening digital infrastructure in the holy sites to ensure the reliability of technological solutions, and encouraging further research into AI-supported interpreting in large-scale religious and humanitarian settings. The study concludes that while AI offers promising opportunities for improving multilingual communication during Hajj, it must be integrated within a hybrid model that maintains human oversight to ensure accuracy, cultural appropriateness, and communicative effectiveness.
Keywords: Artificial Intelligence; Interpreting; Hajj; Communicative Efficiency; Digital Tools